Effect of Different Stages of Chronic Kidney Disease and Renal Replacement Therapies on Oxidant-Antioxidant Balance in Uremic Patients - Hadja Fatima Tbahriti; Abbou Kaddous; Malika Bouchenak; Khedidja Mekki (Biochemistry Research International)
Oxidative stress seems to be involved in the path physiology of cardiovascular complications of chronic kidney disease (CKD). In this study, we determined the effect of different stages of CKD and substitutive therapies on oxidative stress. One hundred sixty-seven patients (age: 44±06 years; male/female: 76/91) with CKD were divided into 6 groups according to the National Kidney Foundation classification. Prooxidant status was assessed by assaying thiobarbituric acid reactive substances, hydroperoxides, and protein carbonyls. Antioxidant defence was performed by analysis of superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase, vitamin E, Iron, and bilirubin. TBARS and LPO were higher in HD patients compared to other groups (P<0.001), while protein carbonyls were more increased in PD patients. The antioxidant enzymes were declined already at severe stage of CKD and they were declined notably in HD patients (P<0.001). Similar observation was found for vitamin E, Fe, and bilirubin where we observed a significant decrease in the majority of study groups, especially in HD patients (P<0.001). The evolution of CKD was associated with elevated OS. HD accentuates lipid, while PD aggravates protein oxidation. However, the activity of antioxidant enzymes was altered by impaired renal function and by both dialysis treatments.